(untitled) (Modern education and development, 2025)
Meningitis is an acute inflammation of the meninges, the protective membranes covering the brain and spinal cord. It can be caused by bacterial, viral, fungal, or parasitic infections. Meningitis is a serious medical condition that requires prompt diagnosis and treatment to prevent severe complications or death. This article reviews the etiology, clinical presentation, diagnostic approaches, treatment options, and prevention strategies of meningitis.